Tour Service Quality and CHSE on Revisit Intention: The Role of Tourist Satisfaction and Gender - Yuliana, Yayuk; Safina, Wan Dian; Ningsih, Ayu Melati; Kristiana, Vera (Universitas Brawijaya, Indonesia, 2025)
Studies related to revisit intention are important, especially in the post-COVID-19 pandemic era. At that time, many tourism destinations and businesses were destroyed and tended to close, so a strategy was needed to revive revisit intention at tourist destinations in Indonesia. This study aims to provide a tourism marketing perspective on tour service quality, Cleanliness, Health, Safety, and environmental sustainability (CHSE), tourist satisfaction, and gender. Tourist satisfaction as a mediator and gender as a moderator. This study employs a quantitative approach, data collection with a questionnaire, with a sample of domestic tourists. The study was conducted from June to September 2024, using a questionnaire administered directly via Google Forms. The study included 350 respondents; the sample was determined using purposive sampling. Data have been analyzed using Structural Equation Modeling and Multi-Group Analysis with Smart PLS 3.0. This investigation found that both female and male tourists: tour service quality has a positive effect on tourist satisfaction and revisit intention. Meanwhile, for both females and males, the role of CHSE does not significantly affect revisit intention. Tourist satisfaction has a positive effect on revisit intention. The results of the indirect effect show that tourist satisfaction mediates the effects of tour service quality and CHSE on revisit intention, for both males and females. The moderation effect of gender in the relationship between tour service quality, CHSE, and tour satisfaction has a positive influence, but the relationship is not significant.